Iguratimod Inhibits the Aggressiveness of Rheumatoid Fibroblast-Like Synoviocytes - Jin Lin; Ye Yu; Xuanwei Wang; Yini Ke; Chuanyin Sun; Lihuan Yue; Guanhua Xu; Bei Xu; Liqin Xu; Heng Cao; Danyi Xu; Nancy Olsen; et al. (Journal of Immunology Research)
Objective. Iguratimod, a novel disease-modifying anti-rheumatic drug for the treatment of rheumatoid arthritis, has been approved in China and Japan. Here, we aimed to find whether iguratimod can inhibit the aggressive behavior and promote apoptosis of rheumatoid fibroblast-like synoviocytes (RA-FLSs). Methods. The proliferation of RA-FLSs was assessed by 5-ethynyl-2′-deoxyuridine test and Cell Counting Kit-8. Migration and invasion were determined by the wound test and a transwell assay. Apoptosis was tested by flow cytometry. The mRNA expression of matrix metalloproteinases (MMPs) and proinflammatory cytokines in RA-FLSs were measured by quantitative PCR and ELISA. To gain insight into the molecular signaling mechanisms, we determined the effect of iguratimod on the activation of mitogen-activated protein kinases (MAPK) signaling pathways by the cellular thermal shift assay (CETSA) and western blot. Results. Iguratimod treatment significantly reduced the proliferation, migration, and invasive capacities of RA-FLSs in a dose-dependent manner in vitro. MMP-1, MMP-3, MMP-9, Interleukin-6 (IL-6), and monocyte chemoattractant protein-1 mRNA and protein levels were all decreased after treatment with iguratimod. Furthermore, tumor necrosis factor-alpha- (TNF-α-) induced expression of phosphorylated c-Jun N-terminal kinases (JNK) and P38 MAPK were inhibited by iguratimod. Additionally, iguratimod promoted the apoptosis of RA-FLSs. Most importantly, iguratimod was shown to directly interact with JNK and P38 protein by CETSA assay. Moreover, activating transcription factor 2 (ATF-2), a substrate of both JNK and P38, was suppressed by iguratimod. Conclusions. Our findings suggested that the therapeutic effects of iguratimod on RA might be, in part, due to targeting the aggressive behavior and apoptosis of RA-FLSs.